Dna Barcoding Of Malaysian Marine Fish, Phylogenetics And Phylogeography Of The Snappers (Perciformes: Lutjanidae) - Bakar, Adibah Abu (2017)
This study, implemented DNA Barcoding which offers great potential as a reliable identification tool to classify catches in Malaysia. Overall, this study had successfully barcoded a total of 107 species, 69 genera, 36 families and 10 order of commercial Malaysian fishes. It is found that, the snappers, threadfin fishes, parrot fishes and goatfishes sampled were detected to either experience cryptic speciation or consist of unknown/undescribed species. Conventional identification to species level using morphological characters were found to be difficult for this genera especially in cases where juvenile and adult specimens exhibit variation in colouration. Thus, at present, this study exposed that at least one lineage represents a currently unrecognized taxon of the ‘yellow-lined snapper complex.